A characterization of the Manduca sexta serotonin receptors in the context of olfactory neuromodulation. - Andrew M Dacks; Vincenzina Reale; Yeli Pi; Wujie Zhang; Joel B Dacks; Alan J Nighorn; Peter D Evans (PLoS ONE)
Neuromodulation, the alteration of individual neuron response properties, has dramatic consequences for neural network function and is a phenomenon observed across all brain regions and taxa. However, the mechanisms underlying neuromodulation are made complex by the diversity of neuromodulatory receptors expressed within a neural network. In this study we begin to examine the receptor basis for serotonergic neuromodulation in the antennal lobe of Manduca sexta. To this end we cloned all four known insect serotonin receptor types from Manduca (the Ms5HTRs). We used phylogenetic analyses to classify the Ms5HTRs and to establish their relationships to other insect serotonin receptors, other insect amine receptors and the vertebrate serotonin receptors. Pharmacological assays demonstrated that each Ms5HTR was selective for serotonin over other endogenous amines and that serotonin had a similar potency at all four Ms5HTRs. The pharmacological assays also identified several agonists and antagonists of the different Ms5HTRs. Finally, we found that the Ms5HT1A receptor was expressed in a subpopulation of GABAergic local interneurons suggesting that the Ms5HTRs are likely expressed heterogeneously within the antennal lobe based on functional neuronal subtype.